Serious liver disease induced by infliximab (2006)
Infliximab, a chimeric monoclonal antibody that binds the tumor necrosis factor ? (TNF?), is used in the treatment of rheumatoid arthritis (RA) and Crohn’s disease (CD). Previous cases of significant secondary liver disease associated with infliximab treatment have been reported in patients with RA, CD, and psoriatic arthritis. Two additional patients with RA who developed a serious liver disease associated with infliximab treatment are reported here. A 39-year old RA patient was admitted with cholestatic liver disease after 8 months of treatment with infliximab. She had no history of hepatic diseases, exposure to hepatotoxic or illicit drugs, or alcohol abuse. A liver biopsy showed severe ductal proliferation with collapse and enucleation of the hepatocytes. Despite aggressive treatment with oral prednisolone, she developed hepatic failure. On the 45th day, a liver transplant was performed. The second patient, a 54-year old RA patient, was diagnosed with autoimmune hepatitis after 12 infliximab infusions. She fulfilled autoimmune hepatitis type 1 criteria. A liver biopsy disclosed an altered lobulillar structure with chronic inflammation and the formation of collagen bands. She was treated with prednisolone and azatioprine and a complete recovery was noted 1 month later. These cases should alert rheumatologists to the possibility of new adverse reactions (liver injury) associated with the use of TNF? blockers in an autoimmune setting.